تطبيقات أنظمة قواعد المعطيات وتقنيات الاتصالات في الخدمات الطبية العلاجية - علي صادق; داؤد ربى (Latakia University Journal -Engineering Sciences Series, 2017)
الهدف من هذا البحث هو تقديم خدمة المرضى من خلال الاستفادة من تطبيقات قواعد المعطيات وأيضاً تطبيقات أنظمة الاتصالات المتاحة والمتوفرة , في الخدمات الطبية وبخاصة العلاجية منها, بحيث يمكننا قدر الإمكان تفادي ما يمكن تفاديه من الكوارث الصحية التي يمكن أن يتعرض لها الإنسان المريض بشكل فجائي. درسنا في هذا البحث كيفية الاستفادة من التقنيات الحديثة في ضبط ومعالجة بعض العلامات الحيوية للإنسان وبخاصة الذين يعانون من بعض المشاكل الصحية المتعلقة ببعض الأمراض , وإبقاءها تحت السيطرة بهدف جعل الأوضاع الصحية لهؤلاء المرضى مستقرة. العلامات الحيوية التي قمنا بتطبيق الدراسة عليها هي : ضغط الدم – نبض القلب– سكر الدم. إذ ان حدوث أي خلل في إحدى قيم تلك العلامات ( زيادة أو نقصانا ) قد يؤدي إلى اصابة المريض بعارض صحي مفاجئ The purpose of this study is to offer help to patients through the employment of databases applications of existing and available telecommunication systems in medical services ,particularly treatment. So that it can be possible to avoided what can be avoided of health disasters that a human being encounter without warning. This study examines how modern technologies can be employed in controlling and processing some vital signs of human beings,particulary those who suffer some health problems affiliated with some diseases ,and keeping these problems under control in order to maintain the stability of the patients health statues. The vital signs that the study is applied to are blood pressure, pulse and blood glucose, since any of change in the value of any of these signs, positive or negative, may cause the patient to have a sudden health problems.